Optimal Portfolio and the Integrated Strategy - Purwanto, Budi; Prima Respati; Nanda Karunia Amanah (Management Analysis Journal, 2024)
The concept of an optimal portfolio is fundamental to investment management, focusing on maximizing returns for a given level of risk. Modern Portfolio Theory (MPT), introduced by Markowitz, has significantly transformed the understanding of risk and return, highlighting the importance of diversification. Nevertheless, constructing an optimal portfolio is a continuous process that demands adaptability and a thorough comprehension of financial markets. This study investigates various approaches, including sectoral, regional, and contrarian stock-based strategies, as well as rebalancing techniques. Additionally, it examines the role of Islamic financial instruments in portfolio management. The results emphasize the necessity of dynamic portfolio management, considering market conditions and the specific objectives of investors. By developing hypotheses and conducting empirical research, this study offers practical insights for investors aiming for optimal performance across different market scenarios. The research underscores the importance of aligning portfolio strategies with changing market dynamics and investor goals, ensuring that portfolios remain well-positioned to achieve desired outcomes. The study’s comprehensive analysis of diverse strategies and instruments provides valuable guidance for investors in navigating the complexities of the financial markets and achieving sustainable investment success.